Rancang Bangun Sistem Informasi Recruitment Karyawan Pada PT. Asta Pilar Gemilang Jakarta - Suryanto, Ade; Dinul, Muhammad (UNISTEK, 2021)
The role and presence of technology today is very much needed, especially for companies engaged in the service sector. Computerized systems and integrated with other systems will greatly help support the company's wheels and be able to compete with other companies. PT Asta Pilar Gemilang Jakarta is currently still running a manual system in recruiting its employees, so the process from initial recruitment to employee selection takes a long time, and information on the availability of existing job vacancies is only through word of mouth (MOM). The best solution to the existing problems is by designing a web-based employee recruitment information system. Applicants can immediately send and fill out their profiles to the system provided, so that companies will be able to see applicants' data in real time and can immediately select and provide information to applicants. This system is built with the Waterfall system development method, and is designed responsively through bootstrap technology, for system devices using UML with the PHP programming language and MySQL database to accommodate data. With this system is expected to provide convenience, effectiveness and efficiency for companies in providing a decision and comfort for job seekers.